ANALISIS SWOT KINERJA SISTEM PENGOLAHAN AIR LIMBAH (IPAL) RUMAH SAKIT UMUM Dr. SOEDARSO PONTIANAK - Anggraini, Sri; Asmadi, Asmadi; Trisnawati, Elly (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2014)
Hospital as the health centers and health education institutions and research has both positive and negative impacts on the surrounding environment. One of the negative impacts is wastewater resulted from the activities of the hospital. Therefore, the waste must be processed by using wastewater treatment plants (WWTPS). Unfortunately , WWTPs at Soedarso Hospital do not work well and can't be functioned properly.Â The study is aimed at analyzing the performance of wastewater treatment plants by using SWOT analysis at Dr. Soedarso Hospital of Pontianak.An observational analytical design (non-experimental) and cross sectional approach were carried out in this study.Â The study revealed that the waste water resulted from data and direct observation showed that the results of the study show the value before treatment was 8.458 pH, BOD was 135.59 mg / L, COD seblum processing is 569.5 mg / L, and TSS treatment is 28 mg / L. There are several problems including malfunctioning of the WWTP. The strengths of the WWTPs were due to the availability of human resources, job descriptions, standard of operations, and facilities and infrastructure of waste management. The opportunities were due to the training center and the regulation of health minister about the health standard of the hospital. The weaknesses of the WWTPs were the lack of interest of the workers to join the training, the less detailed planning of waste management, the lack of compliance to the standards of waste management, the dysfunctional of the WWTPs, and the lack of electrical energy of the pump. While the threat was the parameter of wastewater which exceeded the quality standard NAB based Kep. No. Men LH. 51 1995Â Based on the findings, it is highly recomended that Dr. Soedarso Hospital should utilize a solid organizational structure and create independent installation, improving the quality human resources by offering education opportunities for workers and providing facilities and infrastructure in accordance with the regulatory standards of the Health Minister, and preparing SOP management of waste water based on the regulations of Minister of Health of the Republic of Indonesia.